Learning Strategies of Local Cultural Literacy in Early Chidhood (THUFULA, 2023)
The rapid development of the times resulted in the displacement of local culture. Literacy is present as one of the steps to foster a sense of love for the local local culture. The purpose of this study is to describe learning strategies of local cultural literacy in early childhood. This study uses a qualitative approach, with descriptive analysis method. The subjects of the study were 40 children from grades B1 and B2 and 8 teachers, and school principals at the KB TK Islam Al-Azhar 54 Pekanbaru, which were determined by the researchers by purposive sampling. The data analysis technique uses the interactive model from Milles and Huberman, through the stages of data collection, data reduction, data presentation, drawing conclusions and verification. The results of the research show the need for a conducive environment, interesting methods and media, adequate facilities and infrastructure, as well as teachers who are always creative and innovative. A strategy is needed so that the goals to be achieved can be more easily implemented. The implications of the strategies undertaken will help increase children's understanding of Malay culture, improve children's language skills, creativity and curiosity so that they become quality individuals in the future. The role of parents is also very large in fostering a sense of love for local culture, especially Malay Riau.